PENOLAKAN MENJADI AHLI WARIS DALAM PERSPEKTIF HUKUM ISLAM DAN KUHPERDATA - Parenanda, Janmadika Triwardana (VARIA HUKUM, 2023)
Refusal to become an heir is one of the things that is possible in the Civil Code. The reluctance to take care of the inheritance, the amount of debt left behind, to the desire to give their inheritance to other heirs who need it more is one of the many reasons put forward by the heirs for refusing. However, the concept of refusal of this kind is not found in Islamic inheritance law. Even though the reasons above do not rule out the possibility of being experienced by Muslim heirs. Therefore this paper aims to analyze the refusal to become an heir in the perspective of Islamic law and the Civil Code. This paper uses a normative juridical research method with three (3) approaches namely, statutory approach (statute approach), conceptual approach (conceptual approach) and comparative approach (comparative approach). The conclusion that the author draws is that the Islamic inheritance system does not recognize any refusal to become an heir because the inheritance system uses the principle of ijbari. While in kuperdata, warus can refuse to become heirs as long as the refusal is made expressly before the court where the inheritance is.AbstrakPenolakan menjadi ahli waris merupakan salah satu hal yang dimungkinkan dalam KUHPerdata. Adanya keengganan mengurus harta waris, besarnya hutang yang ditinggalkan, hingga keinginan untuk memberikan harta waris miliknya kepada ahli waris lain yang lebih membutuhkan merupakan salah satu dari sekian banyak alasan yang diajukan ahli waris untuk melakukan penolakan. Akan tetapi kosnep penolakan semacam ini tidak ditemui dalam hukum kewarisan islam. Padahal alasan-alasan diatas tidak menutup kemungkinan juga dialami oleh pewaris muslim. Oleh karenanya tulisan ini bertujuan untuk menganalisis penolakan menjadi ahli waris dalam prespektif hukum islam dan KUHperdata. Tulisan ini menggunakan metode penelotian yuridis normatif dengan tiga (3) pendekatan yakni , pendekatan perundang-undangan (statute approach), pendekatan konseptual (conceptual approach) dan pendekatan perbandingan (comparative approach). Adapun kesimpulan yang penulsi ambil adalah sitem kewarisan islam tidak mengenal adanya penolakan menjadi ahli waris karen sistem pewrisanya menggunakan asas ijbari. Sementara dalam kuperdata, ahli warus bisa melakukan penolakan menjadi ahli waris selama penolakan tersebut dilakukan secara tegas di hadapan Pengadiln dimana harta warisan tersebut.